UNDERSTANDING CULTURE TROUGH CROSS-CULTURAL STUDIES - Willson Gustiawan (Jurnal Ilmiah Poli Bisnis, 2020)
The purpose of this paper is to review some related academic papers to understand cross-cultural concepts. It begins with a briefly introduction to culture definition, the relation of culture and international business, the Culture’s consequences after 25 years; something old and new in cross-cultural studies and a failure of analysis in cross-cultural studies. Then, deeply understanding to cross-cultural studies, it discusses the cross-cultural research in terms of the types, the key issues, problem and proposed solutions, and the process. This paper ends with methodological concepts and theoretical frameworks of universal dimensions of cultural variability. Tujuan dari makalah ini adalah untuk mengutarakan beberapa artikel akademik yang berkaitan untuk memahami konsep lintas budaya (cross-culture). Makalah ini dimulai dengan pengantar singkat mengenai definisi budaya, budaya dan hubungannya dengan bisnis internasional, culture’s consequences karya Hofstede setelah 25 tahun, beberapa hal baru dan lama dalam studi lintas budaya, dan kesalahan analisis dalam studi lintas budaya. Untuk lebih memahami studi lintas budaya, makalah ini mendiskusikan penelitian-penelitian lintas budaya dalam hal tipe-tipe, masalah-masalah kunci, permasalahan dan solusi yang disarankan, serta proses penelitian. Makalah ini diakhiri dengan konsep metodologi dan kerangka teoretis dari berbagai dimensi budaya.